2019
DOI: 10.3390/medicina55050207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus Plantarum and Lactobacillus Helveticus on Renal Insulin Signaling, Inflammatory Markers, and Glucose Transporters in High-Fructose-Fed Rats

Abstract: Background and Objectives: The excess consumption of fructose in the diet may cause metabolic syndrome, which is associated with an increased risk of kidney disease. There is limited data on probiotic treatment in high-fructose-induced metabolic syndrome. The present study aims to investigate whether the supplementation of Lactobacillus plantarum (L. plantarum) and Lactobacillus helveticus (L. helveticus) could provide an improving effect on the renal insulin signaling effectors, inflammatory parameters, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
(68 reference statements)
3
20
1
1
Order By: Relevance
“…The results showed that intake of L. plantarum significantly reduced the TNF-α level, which is in conformity with a previous study showing the supplementation of L. plantarum lowered the TNF-α concentration in male Wistar rats having metabolic syndrome ( 40 ). In addition, ingesting L. plantarum C4 could inhibit TNF-α production in male BALB/c mice after moderate physical exercise ( 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that intake of L. plantarum significantly reduced the TNF-α level, which is in conformity with a previous study showing the supplementation of L. plantarum lowered the TNF-α concentration in male Wistar rats having metabolic syndrome ( 40 ). In addition, ingesting L. plantarum C4 could inhibit TNF-α production in male BALB/c mice after moderate physical exercise ( 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…Other corroborating evidences are the increased inflammatory markers (NF-κB, TNFα, IL-6, and IL-10) reported in cortical tissues of murine diabetes models [201][202][203], HK2 cell cultures under high glucose environment (NF-κB) [204], and cortical portions of T2D patients (NF-κB) [202]. These elevated markers were associated with disrupted insulin signalling characterized by high FOXO1 and reduced AKT [202], PPARγ, and ISRS1 [201,203] but maintained ISR2 levels [201]. Increased renal gluconeogenesis [202], as expected, and reduced GLUT2 [203] were also associated with enhanced inflammatory markers.…”
Section: Glucose Effects On Renal Glucosesupporting
confidence: 54%
“…It was reported that insulin raises SGLT2 protein availability and activity independently of glucose and additionally regulates SGLT2i bioavailability [140][141][142]. Differences in IRec density along the nephron [46] and in the type of IRS expressed in diverse tubule segments, or the same segment but under distinct insulin sensitivity [27,191,[199][200][201]203], point to a renal site-specific selective insulin action and, possibly, to a spatial selective insulin resistance.…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
“…The above strains have been studied in experimental and animal models [ 75 , 76 , 77 , 78 , 79 ] as well as a few clinical studies assessing the functioning of microbiota–gut–brain axis, both in healthy subjects and depressed patients [ 80 , 81 , 82 , 83 ]. Moreover, in an animal model of MetS elevations in tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-6, and IL-10, as well as expression of IL-6 mRNA, were attenuated in L. helveticus -treated rats [ 84 ]. Additionally, recent evidence suggests that intestinal Bifidobacterium species (spp.)…”
Section: Discussionmentioning
confidence: 99%